2002
DOI: 10.1021/ol017117s
|View full text |Cite
|
Sign up to set email alerts
|

H-Bonding Additives Act Like Lewis Acid Catalysts

Abstract: [reaction: see text] A combination of NMR, IR, and ab initio techniques reveals the striking structural similarities of an exemplary H-bonded complex of an N-acyloxazolidinone with an N,N'-disubstituted electron-poor thiourea and the corresponding Lewis acid complex. Although the H-bond association constant is lower than for the Lewis acid adduct, Diels-Alder reactions are accelerated and stereochemically altered in a fashion similar to weak Lewis acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
242
0
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(257 citation statements)
references
References 29 publications
5
242
0
10
Order By: Relevance
“…Based on the results of the reported thioureacatalyzed reactions, [10][11][12][13][14] a variety of bifunctional amino thioureas such as 2a-c were designed by replacing one of the aryl rings of diaryl thiourea 1 by cyclic and acyclic 2-(N,N-dimethylamino)ethane derivatives as a chiral scaffold. To compare the reactivity and selectivity between thiourea and amide, bifunctional amide 2d was also prepared (Fig.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the reported thioureacatalyzed reactions, [10][11][12][13][14] a variety of bifunctional amino thioureas such as 2a-c were designed by replacing one of the aryl rings of diaryl thiourea 1 by cyclic and acyclic 2-(N,N-dimethylamino)ethane derivatives as a chiral scaffold. To compare the reactivity and selectivity between thiourea and amide, bifunctional amide 2d was also prepared (Fig.…”
Section: )mentioning
confidence: 99%
“…Recently, hydrogen-bond donors such as ureas/thioureas, [10][11][12][13][14][15][16][17][18][19][20][21][22][23] BINOL/diols, [24][25][26][27][28][29][30][31][32] and phosphoric acids [33][34][35][36][37][38][39][40] have been also recognized as efficient organocatalysts. Novel urea and thiourea derivatives were developed as organocatalysts and their potential as a general acid has been successfully demonstrated by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Schreiner has employed a thiourea (25 mol % loading) to activate oxazolidinones (complex I, Figure 1) for Diels-Alder reactions. [4] Philp has shown that a diamidopyridine (100 mol %) activates maleimide (complex II, Figure 1) for 1,3-dipolar cycloadditions. [5] Göbel reported that amidinium ions (25 -100 mol %) were capable of activating 1,2-diketones (complex III, Figure 1) for Diels-Alder reactions, [6] and a sulfonamide has been used to accelerate the addition of pyrrolidine to 2(5H)-furanone, presumably via complex IV (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various carbonyl group reactions catalyzed by urea or thiourea compounds have been developed. [15][16][17][18][19][20][21][22] At the outset of our studies for developing new chiral urea and/or thiourea catalyst of the hetero-Micahel reaction, we investigated the reaction of pyrrolidine (2) with g-crotonolactone (3) in the presence of the simple ureas 5 and 7, 17) thioureas 6 and 8, 17) and guanidine 9 as catalysts (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%